2023
DOI: 10.1038/s41598-023-29592-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate change on temperature and precipitation in the Lake Toba region, Indonesia, based on ERA5-land data with quantile mapping bias correction

Abstract: Climate change is a serious problem that can cause global variations in temperature and rainfall patterns. This global variation can affect the water availability of lakes. In this study, trends in temperature and rainfall in the Lake Toba area for 40 years (1981–2020) were analyzed using ERA5-Land data corrected with observation station data utilizing the quantile mapping bias correction method. Corrected ERA5-Land data were used in this study to show spatial patterns and trends. The Mann–Kendall and Sen slop… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 52 publications
0
3
0
1
Order By: Relevance
“…We used the distribution (Quantile-Quantile) mapping bias correction method to reduce the bias in these datasets and making them consistent with the observed datasets. The distribution mapping method efficiently reduces bias for mean and interannual variations and also for extreme events 48 . Aadhar & Mishra 27 compared linear scaling 27 , 49 , 50 and distribution mapping 43 , 50 for the bias correction of precipitation and temperature over South Asia and demonstrated that distribution mapping performs better than the linear scaling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the distribution (Quantile-Quantile) mapping bias correction method to reduce the bias in these datasets and making them consistent with the observed datasets. The distribution mapping method efficiently reduces bias for mean and interannual variations and also for extreme events 48 . Aadhar & Mishra 27 compared linear scaling 27 , 49 , 50 and distribution mapping 43 , 50 for the bias correction of precipitation and temperature over South Asia and demonstrated that distribution mapping performs better than the linear scaling.…”
Section: Methodsmentioning
confidence: 99%
“…ERA5-Land reanalysis is also a combined product of weather models and observations from the satellite and in-situ measurements 37 . Compared to the observed datasets, ERA5-Land reanalysis consists of bias in air temperature 48 . Therefore, the bias correction of ERA5-Land temperature (Raw data) was performed using the observed IMD temperature data (Reference data) at the spatial resolution of 0.25°.…”
Section: Methodsmentioning
confidence: 99%
“…Posteriormente se realizó un análisis de tendencia de la temperatura en la serie de tiempo continuo desde 1980 hasta 2020, con el método Mann-Kendall (Irwandi, Rosid y Mart 2023;Shigute et al, 2023) y usando el nivel de programación de Python, con la librería pymannkendall (Hussain y Mahmud, 2019). La implementación en Python tomó los datos en archivos csv, con columnas como: fecha, época (seca o lluvia), periodo (Niño o Niña) en cada estación estudiada.…”
Section: Análisis De La Información Climáticaunclassified
“…However, the complex human development dynamics make it harder to predict future water availability under unpredictable climatic changes [8]. While climate change analysis is usually focused on evaluating precipitation and temperature trends (e.g., [9]), authors around the world are now including human activities when predicting water resources availability (e.g., [10][11][12]).…”
Section: Introductionmentioning
confidence: 99%